2010
DOI: 10.1021/cg1002379
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Temperature Cycling on Surface Features of Sulfathiazole Crystals during Seeded Batch Cooling Crystallization

Abstract: Published as part of a virtual special issue of selected papers presented in celebration of the 40th Anniversary Conference of the British Association for Crystal Growth (BACG), which was held at Wills Hall,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 41 publications
3
41
0
Order By: Relevance
“…The literature is abundant with reports of organic molecules that display increasing solubility with temperature and procedures that take advantage of this characteristic. Recent examples include Kadam et al (2010), Abu Bakar et al (2010), Svang-Ariyaskul et al (2009), Borissova et al (2009), Eggers et al (2009) and Itoh et al (2008). Recently Black and Jones (2008) and Muller et al (2009) compiled the measured solubility data of several compounds of pharmaceutical interest and found that the solubility approximately doubles every 20 1C.…”
Section: Introductionmentioning
confidence: 99%
“…The literature is abundant with reports of organic molecules that display increasing solubility with temperature and procedures that take advantage of this characteristic. Recent examples include Kadam et al (2010), Abu Bakar et al (2010), Svang-Ariyaskul et al (2009), Borissova et al (2009), Eggers et al (2009) and Itoh et al (2008). Recently Black and Jones (2008) and Muller et al (2009) compiled the measured solubility data of several compounds of pharmaceutical interest and found that the solubility approximately doubles every 20 1C.…”
Section: Introductionmentioning
confidence: 99%
“…The FBRM typically measures thousands of chord lengths per second within different size ranges and this translates to a chord length distribution (CLD) (Barrett and Glennon, 1999). Earlier studies have shown that the CLD data provided by FBRM gives an approximate correlation to the crystal size distribution (CSD), which makes it useful for following the evolution of crystal size within a slurry (Abu Bakar et al, 2010). The emergence of various crystallisation monitoring techniques such as the FBRM has enabled the acquisition of information not only limited to properties such as crystal size distribution, polymorphic forms and purity, which have a profound effect on the quality of final products and further downstream processes, but have also allowed one to follow the crystallisation mechanisms which continuously evolve throughout the entire process (Nagy et al, 2013).…”
mentioning
confidence: 99%
“…The cooling/heating or antisolvent/solvent addition rates can be predetermined, or for more accurate control they can be functions of the difference between the measured and target counts per second ( Figure 5). The benefits of the DNC approach have been demonstrated for the production of crystals with desired mean size (118-119), reduction of solvent inclusion (120), achievement of better polymorphic purity (73), and improvement of the surface properties of the crystals (72). A typical time-domain operating profile with the characteristic automatically determined heatingcooling cycles in the case of the unseeded cooling crystallization of paracetamol in isopropanol is shown in Figure 6a.…”
Section: Promising Research Directions Robust Model-free Control Of Cmentioning
confidence: 99%